Islamic Philanthropy In Indonesia: A Bibliographic Analysis of Its Regulation and Practice - Adinugraha, Hendri Hermawan; Shultoni, Muhammad; Adella, Desy; Al-Kasyaf, Muhammad Zheeva (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research analyzes the role of Islamic philanthropy in Indonesia through a bibliographic approach, examining its contributions, trends, and challenges. A literature review collected data from scholarly sources such as journals, books, and research reports, focusing on publications from the last 5–10 years to ensure relevance. Findings show that Islamic philanthropy—zakat, infaq, sadaqah, and waqf (ZISWAF)—is crucial in poverty alleviation and community empowerment. Research trends indicate a surge in publications after 2015, particularly during the COVID-19 crisis (2020–2021), highlighting ZISWAF’s role in emergencies. Key challenges include low public literacy in waqf, technological barriers, and a lack of transparency in fund management. This study recommends digitalization, improved fund management, and stronger collaboration between the government and private sector to enhance impact. The novelty of this research lies in its bibliographic approach, which identifies research trends and gaps. By addressing existing challenges, Islamic philanthropy can play a more significant role in sustainable development in Indonesia.Keywords: Islamic philanthropy, regulation, bibliographic analysis, and Indonesia.